Uma abordagem comunicacional sobre questões de reconhecimento: jovens em comunidades sustentáveis - Medeiros, Rafael Ferreira (2024)
This thesis aims primarily to comprehend how experiences of denied recognition in different social universes may have contributed to young people's pursuit of affective interactions, rights, and social esteem in sustainable communities, and what role mediations play in the process of change. The study focuses on youth due to the effects that cyclical crises caused by the capitalist system exert on young people, generating forms of disrespect, injustices, and denial of recognition that affect their aspirations, expectations, identities, and social relations. Within the field of communication studies, the research is linked to the assumptions of Latin American cultural studies, understanding communicational processes as cultural linkages in their broad sense, as sites of dialogue and symbolic disputes, including over recognition. The theoretical-methodological formulation developed for this work articulates Bernard Lahire's dispositionalist theory, Axel Honneth's theory of recognition, and Jesús Martín-Barbero's theory of mediations. In the empirical instance, biographical interviews were conducted with four young residents of sustainable communities in order to verify, in their behaviors, lived experiences, social media uses, and mediations activated in different socializing universes and historical contexts, dispositions that contributed to their decision to move to these communities. Based on the interviews and the reconstruction of the life trajectories of these young people, it was possible to perceive that the motivations that led them to migrate to sustainable communities are inscribed in contextual and relational dispositions linked to experiences of denied recognition in the spheres of affect, rights, and social esteem. The linkages of social media uses for recognition and for youth dispositions are perceptible in the contextual relationship with forms of sociability and identity construction. In addition to presenting themselves as a possibility to fill gaps in intersubjective recognition, it is understood that sustainable communities represent for these young people a place to confront the relative frustration arising from the social anomalies caused by the dominant system and an alternative to the ideology of the current capitalist consumer society.